2020
DOI: 10.1186/s12904-020-00692-0
|View full text |Cite
|
Sign up to set email alerts
|

Hospice care self-efficacy among clinical medical staff working in the coronavirus disease 2019 (COVID-19) isolation wards of designated hospitals: a cross–sectional study

Abstract: Background The COVID-19 pandemic has caused more than 462,417 deaths worldwide. A large number of patients with severe COVID-19 face death in hospital. Hospice care is truly a philosophy of care that delivers patient-centred care to the terminally ill and their families. Hospice care could provide many benefits for patients, families, and for hospice caregivers. The aim of this study is to investigate hospice care self-efficacy and identify its predictors among Chinese clinical medical staff in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…A cross-sectional study among clinical nurses and physicians providing hospice care to dying COVID-19 patients in China reported moderate hospice care self-efficacy, results consistent with the current study. 19 Another study conducted in Jordan also agrees with our study findings as it reported moderate levels of self-efficacy among HCWs during caring for COVID-19 patients. 35 However, a study investigating the general self-efficacy of Chinese nurses in the face of COVID-19 during February 2020, reported lower self-efficacy compared to this study.…”
Section: Discussionsupporting
confidence: 91%
“…A cross-sectional study among clinical nurses and physicians providing hospice care to dying COVID-19 patients in China reported moderate hospice care self-efficacy, results consistent with the current study. 19 Another study conducted in Jordan also agrees with our study findings as it reported moderate levels of self-efficacy among HCWs during caring for COVID-19 patients. 35 However, a study investigating the general self-efficacy of Chinese nurses in the face of COVID-19 during February 2020, reported lower self-efficacy compared to this study.…”
Section: Discussionsupporting
confidence: 91%
“…During the prolonged COVID-19 pandemic, however, physical exhaustion and psychological burnout of medical professionals at the frontline are increasing [ 5 , 6 ]. In other words, reports of mental suffers among medical professionals at the COVID-19 frontline including perceived stress [ 7 ], anxiety [ 8 10 ], insomnia [ 11 , 12 ], depressive mood [ 13 ], reduced self-efficiency in medical practice [ 14 ], traumatic or stress-related disorders [ 15 ], or suicidal ideation [ 16 ] have been increasing. First, in terms of the demographic features, younger-aged medical professionals in their earlier stage of career (with fewer years of work experience) and who provide direct care for the infected patients could be more vulnerable for the poor mental health outcome [ 10 , 15 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Effective care can promote health and the art of nursing is mainly expressed through caring [22]. A study has have shown that nursing care is positively correlated with satisfaction; the higher the frequency of nurses having caring behavior, the higher would be the satisfaction of patients with nursing care [12]. Ling et al [2] suggested that the priority of palliative care was to provide patients and their families with comfort, the satisfaction of needs, a healthy environment, emotional support, protection of privacy, and respect.…”
Section: Discussionmentioning
confidence: 99%
“…The main obstacles for nurses to take care of the patients at the end of their lives include their low awareness of palliative care guidance, lack of education and training for palliative care by hospitals, and lack of participation by most of the nurses in palliative care education courses, thereby affecting their nursing guidance ability [11]. According to a survey by Zheng et al [12], the working years, the past behavioral experience of end-stage nursing, and the perceived importance of nurses are positively correlated with the self-e cacy of palliative care. However, P ster et al [13] found that the hospice care knowledge and self-e cacy were positively and negatively correlated with the work experience, respectively.…”
Section: Introductionmentioning
confidence: 99%